Photocurable composition and method for manufacturing camera module
By using a specific ratio of olefin compounds and thiol compounds in the photocurable composition, combined with fillers and colorants, and controlling the refractive index difference, the problem of reduced deep curability after the addition of colorants is solved, and high-depth curing and high-efficiency curing are achieved. effect on bond strength.
Patent Information
- Application Number
- CN202380045337.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-06
- Filing Date
- 2023-06-02
- Publication Date
- 2025-01-21
AI Technical Summary
After the colorant is added to the conventional photocurable composition, the deep curability of the deep curable properties are easily reduced, and it is difficult to maintain a good curing effect.
By adding a specific ratio of olefin compounds and thiol compounds to the photocurable composition, and combining fillers and colorants, the refractive index difference between the reaction curable resin component and the filler is controlled within a specific range to suppress the scattering of light and improve Deep curability.
In the case of adding a color to the composition, maintain a good deep solidivity and improve the blackness and adhesion strength of the curing.
Smart Images

Figure BDA0005173595280000031 
Figure BDA0005173595280000221 
Figure BDA0005173595280000222
Abstract
Description
Technical Field
[0001] The present disclosure relates to a photocurable composition and a method for manufacturing a camera module, and more particularly to a photocurable composition containing an ene compound and a thiol compound, and a method for manufacturing a camera module using the photocurable composition. Background Art
[0002] Patent Document 1 discloses a resin composition containing an acrylic resin, a thiol compound, a latent curing agent, a radical polymerization inhibitor, and an anionic polymerization inhibitor.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent No. 4976575 Summary of the invention
[0006] Problem that the invention aims to solve
[0007] The present disclosure provides a photocurable composition and a method for manufacturing a camera module using the photocurable composition. The photocurable composition contains an ene compound and a thiol compound and contains a colorant, but has good deep curability.
[0008] A photocurable composition according to one embodiment of the present disclosure comprises: a reaction curable resin component containing an ene compound (A) and a thiol compound (B), a filler (C), a colorant (D), and a radical polymerization initiator (E). When the refractive index of the reaction curable resin component is dr and the refractive index of the filler (C) is df, dr and df satisfy the relationship represented by the following formula (1).
[0009] -0.040<(df-dr)≤0.080 (1)
[0010] A method for manufacturing a camera module according to one embodiment of the present invention is a method for manufacturing a camera module having an optical component and a component other than the optical component, namely a peripheral component. The aforementioned manufacturing method includes an operation of bonding the aforementioned optical component and the aforementioned peripheral component using an adhesive. The aforementioned adhesive is a photocurable composition containing a reaction-curable resin component, a filler (C) and a colorant (D). When the value of the refractive index of the aforementioned reaction-curable resin component is set to dr, and the value of the refractive index of the aforementioned filler (C) is set to df, dr and df satisfy the relationship shown in the following formula (1).
[0011] -0.040<(df-dr)≤0.080 (1) DETAILED DESCRIPTION
[0012] The development process of the present disclosure will be roughly described.
[0013] A photocurable composition containing an ene compound and a thiol compound is sometimes used as an adhesive. In addition, depending on the application, the adhesive is sometimes colored by mixing a colorant. According to the investigation of the present inventors, if a colorant is mixed in a photocurable composition containing an ene compound and a thiol compound, the deep curability of the composition is likely to be greatly reduced.
[0014] Therefore, the present inventors conducted research and development to obtain a photocurable composition containing an ene compound and a thiol compound and having good deep curability despite containing a colorant, and thus completed the present disclosure.
[0015] It should be noted that, although the present disclosure is completed due to the above process, the above process does not limit the form, application, etc. of the present disclosure, and the content of the present disclosure can be determined according to the configuration of the present disclosure.
[0016] Hereinafter, an embodiment of the present disclosure will be described. It should be noted that the following embodiment is only one of the various embodiments of the present disclosure. As long as the purpose of the present disclosure can be achieved, the following embodiment can be variously changed according to the design.
[0017] The photocurable composition of the present embodiment (hereinafter also referred to as composition (X)) comprises: a reaction curable resin component containing an olefin compound (A) and a thiol compound (B), a filler (C), a colorant (D) and a radical polymerization initiator (E). When the refractive index of the reaction curable resin component is dr and the refractive index of the filler (C) is df, dr and df satisfy the relationship shown in the following formula (1).
[0018] -0.040<(df-dr)≤0.080 (1)
[0019] That is, the value of (df-dr) is larger than -0.040 and smaller than or equal to 0.080.
[0020] Therefore, according to the present embodiment, although the composition (X) contains a colorant (D), the photocurable composition can still have good deep curing properties. Furthermore, the appearance of the cured product obtained by photocuring the composition (X) will easily become black. The reasons can be inferred as follows. It is believed that the degree of scattering of light in the composition (X) is particularly strongly affected by the refractive index difference between the reaction curable resin component and the filler (C). When the refractive index difference is within a specific range, the scattering of light in the composition (X) can be suppressed. When the composition (X) is exposed, the light will become easy to reach the deep part of the composition (X). In addition, the degree of scattering of light in the cured product is also particularly strongly affected by the refractive index difference between the reaction curable resin component and the filler (C) in the composition (X). If the refractive index difference is within a specific range, the scattering of light in the cured product can be suppressed. Therefore, it is believed that the situation that the cured product looks whitish due to the scattering of light can be suppressed, so the appearance of the cured product will easily become black due to the colorant (D).
[0021] The value of (df-dr) is more preferably -0.035 or more, and even more preferably -0.030 or more. Furthermore, the value of (df-dr) is more preferably 0.075 or less, and even more preferably 0.070 or less.
[0022] The reaction-curable resin component refers to a component that cures by chemical reaction, that is, a component having reaction-curability for curing the composition (X). The refractive index dr of the reaction-curable resin component is defined by the following formula.
[0023]
[0024] In this formula, t is the number of types of compounds contained in the reaction curable resin component, and dr n is the refractive index of the nth compound alone, x n is the amount of substance of the nth compound in the composition (X), x all It is the amount of the total amount of the reaction-curable resin component in the composition (X).
[0025] The composition (X) is preferably used as an adhesive, and more preferably used for bonding components in optical devices such as camera modules. It should be noted that when the composition (X) is used as an adhesive, it can be used to bond any article, that is, the use of the composition (X) is not limited to bonding components in optical devices such as camera modules. In addition, when the composition (X) is used as an adhesive, it can also be used to bond materials other than resin materials. In addition, the composition (X) can be applied to purposes other than adhesives, for example, it can also be used as a sealing material for electronic components.
[0026] The details of the components contained in the composition (X) will be described.
[0027] The ene compound (A) and the thiol compound (B) are components having a reaction curing property for curing the composition (X).
[0028] The ene compound (A) and the thiol compound (B) are selected based on their relationship with the filler (C), that is, they are selected so that the refractive index of the reaction-curable resin component containing the ene compound (A) and the thiol compound (B) and the refractive index of the filler (C) have the relationship represented by the above formula (1).
[0029] The olefin compound (A) contains, for example, at least one of a compound having at least one of an acryloyl group and a methacryloyl group (hereinafter referred to as an acrylic compound) and a compound having a vinyl group (hereinafter referred to as a vinyl compound).
[0030] The acrylic compound contains, for example, at least one selected from the group consisting of trimethylolpropane triacrylate, 1,6-hexanediol diacrylate, dimethylol-tricyclodecane diacrylate, acryloyl morpholine, tetrahydrofurfuryl acrylate, 4-hydroxybutyl acrylate, 9,9-bis(4-(2-(meth)acryloyloxyethoxy)phenyl)-9H-fluorene, ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A dimethacrylate, tricyclodecane dimethanol dimethacrylate, tri-(2-acryloyloxyethyl)isocyanurate, bis-(2-acryloyloxyethyl)isocyanurate, caprolactone-modified tri-(2-acryloyloxyethyl)isocyanurate, isocyanuric acid EO-modified diacrylate, and isocyanuric acid EO-modified triacrylate.
[0031] The vinyl compound contains at least one selected from the group consisting of triallyl isocyanurate, allyl glycidyl ether, trimethylolpropane diallyl ether, pentaerythritol triallyl ether and the like.
[0032] The olefin compound (A) preferably contains a compound having an isocyanurate skeleton. In this case, it is easy to improve the bonding strength of the cured product of the composition (X) when the composition (X) is applied to an adhesive. In this case, the olefin compound (A) preferably contains at least one selected from the group consisting of tris-(2-acryloyloxyethyl) isocyanurate, bis-(2-acryloyloxyethyl) isocyanurate, caprolactone-modified tris-(2-acryloyloxyethyl) isocyanurate, isocyanuric acid EO-modified diacrylate, isocyanuric acid EO-modified triacrylate and triallyl isocyanurate.
[0033] The compounds that may be contained in the olefinic compound (A) are not limited to the above-mentioned compounds, and the olefinic compound (A) may contain various compounds having an ethylenically unsaturated bond.
[0034] The molecular weight of the olefin compound (A) is, for example, 80 or more and 1,000 or less.
[0035] The thiol compound (B) preferably contains a compound having at least two thiol groups in one molecule. The thiol compound (B) more preferably contains a compound having three or more and six or less thiol groups in one molecule.
[0036] The thiol compound (B) includes, for example, an ester of a polyol and a mercapto organic acid, and the ester includes at least one of a partial ester and a complete ester.
[0037] The polyol includes, for example, at least one selected from the group consisting of ethylene glycol, trimethylolpropane, pentaerythritol, and dipentaerythritol.
[0038] The mercapto organic acid includes at least one selected from the group consisting of mercapto aliphatic monocarboxylic acids, esters containing a thiol group and a carboxyl group obtained by an esterification reaction between a hydroxy acid and a mercapto organic acid, mercapto aliphatic dicarboxylic acids, and mercapto aromatic monocarboxylic acids. The mercapto aliphatic monocarboxylic acid includes, for example, at least one selected from the group consisting of mercaptoacetic acid; mercaptopropionic acids such as 3-mercaptopropionic acid; and mercaptobutyric acids such as 3-mercaptobutyric acid and 4-mercaptobutyric acid. The carbon number of the mercapto aliphatic monocarboxylic acid is preferably 2 to 8, more preferably 2 to 6, further preferably 2 to 4, and particularly preferably 3. The mercapto aliphatic monocarboxylic acid having a carbon number of 2 to 8 includes, for example, at least one selected from the group consisting of mercaptoacetic acid, 3-mercaptopropionic acid, 3-mercaptobutyric acid, and 4-mercaptobutyric acid. The mercapto aliphatic dicarboxylic acid includes, for example, at least one selected from the group consisting of dimercaptosuccinic acids such as mercaptosuccinic acid and 2,3-dimercaptosuccinic acid. The mercapto aromatic monocarboxylic acid includes, for example, mercaptobenzoic acid such as 4-mercaptobenzoic acid.
[0039] The partial ester of a polyol and a mercapto organic acid includes, for example, at least one selected from the group consisting of trimethylolpropane bis(thioglycolate), trimethylolpropane bis(3-mercaptopropionate), trimethylolpropane bis(3-mercaptobutyrate), trimethylolpropane bis(4-mercaptobutyrate), pentaerythritol tris(thioglycolate), pentaerythritol tris(3-mercaptopropionate), pentaerythritol tris(3-mercaptobutyrate), pentaerythritol tris(4-mercaptobutyrate), dipentaerythritol tetra(thioglycolate), dipentaerythritol tetra(3-mercaptopropionate), dipentaerythritol tetra(3-mercaptobutyrate) and dipentaerythritol tetra(4-mercaptobutyrate).
[0040] Examples of full esters of polyols and mercapto organic acids include ethylene glycol bis(thioglycolate), ethylene glycol bis(3-mercaptopropionate), ethylene glycol bis(3-mercaptobutyrate), ethylene glycol bis(4-mercaptobutyrate), trimethylolpropane tris(thioglycolate), trimethylolpropane tris(3-mercaptopropionate), trimethylolpropane tris(3-mercaptobutyrate), trimethylolpropane tris(4-mercaptobutyrate), pentaerythritol tetra(thioglycolate), pentaerythritol tetra(3-mercaptopropionate), pentaerythritol tetra(3-mercaptobutyrate), pentaerythritol tetra(4-mercaptobutyrate), dipentaerythritol hexa(thioglycolate), dipentaerythritol hexa(3-mercaptopropionate), dipentaerythritol hexa(3-mercaptobutyrate), and dipentaerythritol hexa(4-mercaptobutyrate). Preferably, at least one selected from the group consisting of pentaerythritol tetrakis(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), dipentaerythritol hexa(3-mercaptopropionate) and trimethylolpropane tris(3-mercaptopropionate) is contained.
[0041] The thiol compound (B) may contain, for example, tris[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, 1,3,5-tris(3-mercaptobutoxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and the like.
[0042] The thiol compound (B) may also contain compounds other than the above. For example, the thiol compound (B) may also contain at least one selected from the group consisting of 1,4-butanedithiol, 1,6-hexanedithiol, 1,8-octanedithiol, 1,10-decanedithiol, 3,6-dioxa-1,8-octanedithiol and bis-2-mercaptoethyl sulfide. The thiol compound (B) may also contain at least one selected from the group consisting of tris(3-mercaptopropyl)isocyanurate, 1,3,5-tris[3-(2-mercaptoethylthio)propyl]isocyanurate and 1,3,4,6-tetrakis(2-mercaptoethyl)glycoluril.
[0043] The thiol compound (B) may also contain a compound having a secondary thiol group. For example, the thiol compound (B) may also contain at least one selected from the group consisting of pentaerythritol tetrakis (3-mercaptobutyrate), 1,4-bis (3-mercaptobutyryloxy) butane, 1,3,5-tris (2- (3-thiobutyryloxy) ethyl) -1,3,5-triazine-2,4,6-trione and trimethylolpropane tris (3-mercaptobutyrate). The compound having a secondary thiol group is more likely to improve the storage stability of the composition (X) than the compound having a primary thiol group.
[0044] Relative to the portion after removing the filler (C) from the solid content of the composition (X), the percentage of the sum of the alkene compound (A) and the thiol compound (B) is preferably 70% by mass or more. At this time, the composition (X) can have good reaction curing properties. It is more preferred that the percentage is 80% by mass or more, and it is further preferred that it is 90% by mass or more. In addition, the percentage is, for example, 97% by mass or less. It should be noted that the solid content refers to the components after removing the volatile components in the composition (X). Volatile components refer to components that evaporate during the process of curing the composition (X) to make a cured product and do not constitute a cured product, such as a solvent.
[0045] In addition, regarding the blending ratio of the ene compound (A) and the thiol compound (B), the thiol compound (B) / ene compound (A) equivalent ratio (i.e., the functional group equivalent ratio of the thiol compound (B) to the ene compound (A)) is preferably 0.4 or more and 1.0 or less. It is more preferred that the equivalent ratio is 0.5 or more, and it is further preferred that it is 0.55 or more. In addition, it is more preferred that the equivalent ratio is 0.8 or less, and it is further preferred that it is 0.7 or less.
[0046] The reaction curable resin component in the composition (X) can be only olefin compound (A) and thiol compound (B). In addition, within the scope of not excessively damaging the effect of the present embodiment, the reaction curable resin component in the composition (X) can also contain a component with reaction curability other than olefin compound (A) and thiol compound (B) (hereinafter referred to as component (Y)). When the composition (X) contains component (Y), the percentage of component (Y) relative to olefin compound (A) is preferably greater than 0 mass % and is less than 70 mass %. The percentage is preferably less than 50 mass %, and it is further preferred to be less than 30 mass %. The example of the compound contained in component (Y) includes epoxy compound, oxetane compound, phenol compound and amine compound. The reaction curable resin component also preferably contains epoxy compound.
[0047] The filler (C) is described. The filler (C) only needs to be a granular substance. The filler (C) is selected based on the relationship with the olefin compound (A), that is, the filler (C) is selected so that the refractive index of the olefin compound (A) and the refractive index of the filler (C) have the relationship shown in the above formula (1). When the filler (C) contains multiple substances, it is preferred that when the refractive index of at least one of the multiple substances is regarded as df, the relationship shown in the above formula (1) holds, and it is particularly preferred that even when the refractive index of any substance among the multiple substances is regarded as df, the relationship shown in the above formula (1) still holds.
[0048] The filler (C) may contain at least one of a resin filler composed of an organic resin and an inorganic filler.
[0049] The resin filler can improve the flexibility of the cured product. The resin filler contains, for example, at least one selected from the group consisting of silicone powder, polystyrene powder, acrylic resin powder, benzoguanamine resin powder, polybutadiene powder, and powders containing two or more of the foregoing resins. It should be noted that the resins that the resin filler can contain are not limited to the foregoing.
[0050] The silicone powder contains, for example, at least one selected from the group consisting of the following powders: a powder composed of silicone rubber (silicone rubber powder), a powder composed of silicone resin (silicone resin powder), and a powder having a core composed of silicone rubber and a shell composed of silicone resin (silicone composite powder). It should be noted that silicone resin refers to silicone having a three-dimensional skeleton mainly composed of siloxane bonds, and silicone rubber refers to silicone having a two-dimensional skeleton mainly composed of siloxane bonds.
[0051] Examples of powders containing two or more resins include core-shell powders. One example of core-shell powders includes butadiene core-shell powders having a core containing butadiene rubber and a shell containing an acrylic polymer and covering the core.
[0052] The average particle size of the resin filler is preferably not less than 0.1 μm and not more than 30 μm. When the average particle size is not less than 0.1 μm, there is an advantage that the viscosity of the composition (X) can be suppressed from excessively increasing. When the average particle size is not more than 30 μm, there is an advantage that the high permeability of the composition (X) into a narrow space can be maintained. It is more preferred that the average particle size is not less than 0.11 μm, and it is further preferred that it is not less than 0.12 μm. In addition, it is more preferred that the average particle size is not more than 25 μm, and it is further preferred that it is not more than 20 μm. It should be noted that the average particle size is the particle size (d 50 ).
[0053] The percentage of resin filler relative to composition (X) is preferably 5% by mass or more and 40% by mass or less. When the percentage is 5% by mass or more, it is particularly easy to improve the flexibility of the cured product (X), and it is easy to reduce the curing shrinkage. In addition, when the percentage is 40% by mass or less, there is an advantage that the viscosity of the composition (X) can be suppressed from rising excessively. It is more preferred that the percentage is 10% by mass or more, further preferred that it is 12% by mass or more, and particularly preferred that it is 15% by mass or more. In addition, it is more preferred that the percentage is 35% by mass or less, further preferred that it is 32% by mass or less, and particularly preferred that it is 30% by mass or less.
[0054] Composition (X) reduces the elastic modulus of cured product by containing resin filler, and the tensile elastic modulus of cured product obtained by the measurement result of the tensile test based on JIS K7127 is preferably less than 5.0GPa. That is, preferably in the mode that the tensile elastic modulus of cured product becomes less than 5.0GPa, the composition of composition (X), particularly the kind and compounding amount of resin filler are adjusted within the above range. At this time, the adhesion of cured product can be particularly improved. The tensile elastic modulus of cured product is more preferably less than 4.5GPa, and more preferably less than 4.0GPa. In addition, the tensile elastic modulus of cured product is preferably more than 0.5GPa, and more preferably more than 0.8GPa, and more preferably more than 1.0GPa. It should be noted that the detailed content of the determination method of the tensile elastic modulus of cured product will be described in the column of the embodiment disclosed later.
[0055] When the composition (X) contains an inorganic filler, the curing shrinkage during the curing of the composition (X) to make a cured product becomes less likely to occur. Therefore, the composition (X) becomes more suitable for bonding components in precision equipment such as camera modules. The inorganic filler contains, for example, at least one selected from the group consisting of silica, aluminum oxide, barium sulfate, talc, clay, mica, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum borate, barium titanate, strontium titanate, magnesium titanate, bismuth titanate, titanium oxide, barium zirconate and calcium zirconate.
[0056] The average particle size of the inorganic filler is preferably 0.1 μm or more and 50 μm or less. When the average particle size is 0.1 μm or more, it has the advantage of suppressing excessive increase in viscosity of the composition (X). When the average particle size is 50 μm or less, it has the advantage of maintaining high penetration of the composition (X) into narrow spaces. It is more preferred that the average particle size is 0.2 μm or more, and it is further preferred that it is 0.3 μm or more. In addition, it is more preferred that the average particle size is 45 μm or less, and it is further preferred that it is 40 μm or less. It should be noted that the average particle size is the median particle size (D50) calculated from the particle size distribution obtained according to the dynamic light scattering method.
[0057] The percentage of the inorganic filler relative to the composition (X) is, for example, 0% by mass or more and 90% by mass or less. It is more preferred that the percentage is 5% by mass or more, and it is further preferred that the percentage is 10% by mass or more. In addition, it is more preferred that the percentage is 85% by mass or less, and it is further preferred that the percentage is 80% by mass or less.
[0058] In addition, the percentage of filler (C) as a whole relative to composition (X) is, for example, greater than 0% by mass and less than 90% by mass. The percentage is preferably greater than 5% by mass, and more preferably greater than 10% by mass. In addition, the percentage is preferably less than 85% by mass, and more preferably less than 80% by mass.
[0059] The refractive index of the filler (C) is preferably 1.480 or more and 1.590 or less. At this time, the composition (X) can have better deep curing properties and can further improve the blackness of the cured product. The refractive index of the filler (C) is more preferably 1.485 or more, and more preferably 1.490 or more. In addition, the refractive index of the filler (C) is more preferably 1.585 or less, and more preferably 1.580 or less.
[0060] The true specific gravity of the filler (C) is preferably 0.50 or more and 2.00 or less. If the true specific gravity is 0.50 or more, the difference in specific gravity with the reaction-curable component in the composition (X) becomes smaller, so there is an advantage that the filler (C) in the composition (X) can be suppressed from floating. In addition, if the true specific gravity is 2.00 or less, it becomes difficult to produce an increase in the elastic modulus of the cured product caused by the filler (C), and it becomes difficult to damage the softness of the cured product. It is more preferred that the true specific gravity of the filler (C) is 0.55 or more, and it is further preferred that it is 0.60 or more. In addition, it is more preferred that the true specific gravity of the filler (C) is 1.95 or less, and it is further preferred that it is 1.90 or less.
[0061] When the filler (C) contains a plurality of substances, the true specific gravity of the filler (C) as a whole preferably satisfies the above conditions, and it is more preferred that the plurality of substances contained in the filler (C) respectively satisfy the above conditions.
[0062] The colorant (D) is described. The colorant (D) refers to a material having an L* value of 40 or less in the L*a*b* colorimetric system standardized by the International Commission on Illumination (CIE) in 1976. It should be noted that when the colorant (D) contains a granular material, the granular material is not included in the above-mentioned filler (C). That is, the material contained in the colorant (D) is removed from the filler (C). The colorant (D) preferably contains a black colorant (D1). The black colorant (D1) contains, for example, at least one of a black pigment and a black dye. The black pigment contains, for example, at least one selected from the group consisting of inorganic black pigments such as carbon black, titanium black and zirconium nitride and organic black pigments such as perylene black pigments. Black dyes are commercially available, and contain at least one selected from the group consisting of, for example, Kayaset (registered trademark) manufactured by Nippon Kayaku Co., Ltd., NUBIAN (registered trademark) manufactured by ORIENT CHEMICAL INDUSTRIES CO., LTD., SOPROTONER (registered trademark) manufactured by Sanyo Color Co., Ltd., SEIKAFAST (registered trademark) manufactured by Dainichi Seika Industries Co., Ltd., Spirit (registered trademark) manufactured by Sumika Chemtex Co., Ltd., and AIZEN (registered trademark) manufactured by Hodogaya Chemical. The composition (X) and its cured product can be colored by using the black colorant (D1). In addition, in the present embodiment, even if the composition (X) contains the black colorant (D1), the composition (X) can still have good deep curability.
[0063] The percentage of the black colorant (D1) relative to the solid content of the composition (X) is preferably 1.0% by mass or less. In the present embodiment, even if the percentage of the black colorant (D1) is 1.0% by mass or less, the blackness of the cured product can still be fully improved because the refractive index of the olefin compound (A) and the refractive index of the filler (C) are in a specific relationship. In addition, when the percentage of the black colorant (D1) is 1.0% by mass or less, the deep curability of the composition (X) can be particularly improved. In addition, the percentage of the black colorant (D1) relative to the solid content of the composition (X) is also preferably 0.02% by mass or more. At this time, the blackness of the color of the cured product can be particularly improved. In addition, even if the percentage of the black colorant (D1) is 0.02% by mass or more, the composition (X) can still have good deep curability. It should be noted that the solid content refers to the components of the composition (X), except for the volatile components such as the solvent volatilized from the composition (X) during the process of curing the composition (X) to make the cured product, that is, it refers to the components of the composition (X) that constitute the cured product. The percentage of the black colorant (D1) is more preferably 0.04% by mass or more, and even more preferably 0.06% by mass or more. Furthermore, the percentage is more preferably 0.95% by mass or less, and even more preferably 0.90% by mass or less.
[0064] The colorant (D) may contain a colorant other than the black colorant (D1) (hereinafter also referred to as a colorant (D2)). The colorant (D2) may contain at least one colorant selected from appropriate organic pigments, inorganic pigments, and dyes having a light absorption effect in the visible light region. The colorant (D2) contains, for example, a colorant selected from the group consisting of monoazo pigments, quinacridone, iron oxide yellow, disazo pigments, phthalocyanine green, phthalocyanine blue, cyanine blue, flavanthrone yellow, dianthraquinonyl red, indanthrone blue, thioindigo bordeaux, perinone orange, perylene scarlet, perylene red 178, perylene maroon, dioxazine violet, isoindolinone yellow, quinophthalone, isoindoline yellow, nickel nitroso yellow, and cyanine blue. yellow), madder lake, copper azomethine yellow, alkaline blue, rediron oxide, chromium oxide, titanium yellow, cobalt blue, cerulean blue, cobalt green, alumina white, viridian, cadmium yellow, cadmium red, vermilion, lithopone, chrome yellow, molybdate orange, zinc chromate, ultramarine, manganese violet, cobalt violet, emerald green,At least one of the group consisting of blue, green, dark blue, metallic powder, azo dyes, anthraquinone dyes, indigoid dyes, phthalocyanine dyes, carbonium dyes, quinoneimine dyes, methine dyes, quinoline dyes, nitro dyes, nitroso dyes, benzoquinone dyes, naphthoquinone dyes, naphthalimide dyes and perinone dyes.
[0065] The percentage of the colorant (D) relative to the solid content of the composition (X) is preferably 1.0% by mass or less. The percentage of the colorant (D) relative to the solid content of the composition (X) is also preferably 0.02% by mass or more. The percentage of the colorant (D) is more preferably 0.04% by mass or more, and more preferably 0.06% by mass or more. In addition, the percentage is more preferably 0.95% by mass or less, and more preferably 0.90% by mass or less.
[0066] As described above, the composition (X) contains a radical polymerization initiator (E). The radical polymerization initiator (E) can impart light curing properties to the composition (X). In particular, when the composition (X) is used as an adhesive, after the composition (X) is temporarily bonded by curing it to a certain extent by irradiating it with light, the composition (X) can be fully cured by heating it for formal bonding. In addition, by irradiating the composition (X) with light to fully cure the composition (X), the composition (X) can also be cured without heating to produce a cured product.
[0067] The free radical polymerization initiator (E) contains, for example, at least one compound selected from the group consisting of aromatic ketones, acylphosphine oxide compounds, aromatic onium salt compounds, organic peroxides, thio compounds (thioxanthone compounds, phenylthio-containing compounds, etc.), hexaarylbiimidazole compounds, ketoxime ester compounds, borate compounds, azinium compounds, metallocene compounds, active ester compounds, compounds having a carbon-halogen bond, and alkylamine compounds.
[0068] Relative to the sum of the olefin compound (A) and the thiol compound (B), the percentage of the radical polymerization initiator (E) is preferably 0.05% by mass or more and 3.0% by mass or less. At this time, sufficient photocurability can be given to the composition (X). It is more preferred that the percentage is 0.1% by mass or more, further preferred that it is 0.2% by mass or more, and particularly preferred that it is 0.4% by mass or more. In addition, it is more preferred that the ratio is 2.8% by mass or less, further preferred that it is 2.5% by mass or less, and particularly preferred that it is 2.3% by mass or less.
[0069] The composition (X) may contain an anionic polymerization initiator (F). In this case, the curing reaction of the composition (X) is easily advanced by heating the composition (X).
[0070] The anionic polymerization initiator (F) contains at least one component selected from the group consisting of, for example, imidazoles, cyclic amidines, tertiary amines, organic phosphines, tetrasubstituted phosphonium / tetrasubstituted borates, quaternary phosphonium salts having a counter anion other than borates, and tetraphenylborate.
[0071] The anionic polymerization initiator (F) may also contain a latent curing catalyst (latent anionic polymerization initiator) (F1). In this case, the reaction of the composition (X) in an unheated state can be suppressed, thereby improving the storage stability of the composition (X). The latent curing catalyst (F1) may contain at least one of a liquid latent curing accelerator and a solid dispersed latent curing accelerator. The latent curing catalyst (F1) may also contain a microcapsule type latent curing catalyst (F11). The microcapsule type latent curing catalyst (F11) contains, for example, microencapsulated imidazoles containing imidazoles as a compound having catalytic activity.
[0072] Relative to the sum of the olefin compound (A) and the thiol compound (B), the percentage of the anionic polymerization initiator (F) is preferably 0.1% by mass or more and 35% by mass or less. If the percentage is 0.1% by mass or more, the reactivity of the composition (X) when the composition (X) is reacted and cured can be improved. In addition, if the percentage is 35% by mass or less, the storage stability of the composition (X) can be further improved. It is more preferred that the percentage is 0.3% by mass or more, more preferred that it is 0.5% by mass or more, and particularly preferred that it is 0.8% by mass or more. In addition, it is more preferred that the percentage is 20% by mass or less, more preferred that it is 15% by mass or less, and particularly preferred that it is 10% by mass or less.
[0073] The composition (X) may also contain a stabilizer (G). The stabilizer (G) is a compound that makes it difficult for the reactive components in the composition (X), namely, the ene compound (A) and the thiol compound (B), to react. If the composition (X) contains the stabilizer (G), the storage stability of the composition (X) can be improved.
[0074] The stabilizer (G) preferably contains at least one of a radical polymerization inhibitor and an anionic polymerization inhibitor. In this case, it is easier to improve the storage stability of the composition (X). It is speculated that this is because during the storage of the composition (X), the radical polymerization inhibitor makes it difficult for the radical polymerization reaction between the ene compound (A) and the thiol compound (B) and the radical polymerization reaction between the molecules in the ene compound (A) to proceed, and the anionic polymerization inhibitor makes it difficult for the anionic polymerization reaction between the ene compound (A) and the thiol compound (B) to proceed.
[0075] The radical polymerization inhibitor may contain, for example, at least one compound selected from the group consisting of 4-tert-butylcatechol, tert-butylhydroquinone, 1,4-benzoquinone, dibutylhydroxytoluene, 1,1-diphenyl-2-trinitrophenylhydrazine, hydroquinone, hydroquinone monomethyl ether, p-hydroxyanisole (mequinol), phenothiazine, and N-nitroso-N-phenylhydroxylamine aluminum. It should be noted that the compounds that the radical polymerization inhibitor may contain are not limited to the above.
[0076] In particular, when the composition (X) contains an anionic polymerization initiator (F), the anionic polymerization inhibitor is preferably mixed in the composition (X). At this time, during the storage of the composition (X), the curing reaction in the composition (X) due to the anionic polymerization initiator (F) can be suppressed. The anionic polymerization inhibitor contains, for example, at least one of an organic boronic acid compound and a compound having a phenolic hydroxyl group. The organic boronic acid compound contains, for example, at least one boric acid ester selected from the group consisting of triethyl borate, tributyl borate and triisopropyl borate. The compound having a phenolic hydroxyl group contains, for example, at least one selected from the group consisting of 2,3-dihydroxynaphthalene, 4-methoxy-1-naphthol, 1,2,3-pyrogallol, methylhydroquinone and tert-butylhydroquinone.
[0077] Relative to the sum of alkene compound (A) and thiol compound (B), the percentage of stabilizer (G) is preferably 0.01 mass % or more and 1.5 mass % or less. When the percentage is 0.01 mass % or more, the storage stability of composition (X) can be further improved. When the percentage is 1.5 mass % or less, the curability of composition (X) is not easily damaged, and high bonding strength can be maintained when composition (X) is cured under appropriate conditions. It is more preferred that the percentage is 0.05 mass % or more, and it is further preferred that it is 0.10 mass % or more. In addition, it is more preferred that the percentage is 1.0 mass % or less, and it is further preferred that it is 0.7 mass % or less.
[0078] Composition (X) may also contain carbodiimide compound (H). At this time, the cured product of composition (X) becomes less prone to deterioration even at high temperature and high humidity, and the durability of the cured product can be improved. When composition (X) contains carbodiimide compound (H), relative to the sum of ene compound (A) and thiol compound (B), the percentage of carbodiimide compound (E) is preferably 1% by mass or more and 20% by mass or less. If the percentage is 1% by mass or more, it is particularly easy to improve the reliability of the cured product. If the ratio is 20% by mass or less, it is easy to maintain the deep curing property of the cured product (X). It is more preferred that the percentage is 3% by mass or more, more preferably 5% by mass or more, and 7% by mass or more is particularly preferred. In addition, it is more preferred that the percentage is 15% by mass or less, more preferably 12% by mass or less, and 10% by mass or less is particularly preferred.
[0079] The carbodiimide compound (H) refers to a compound having a carbodiimide group (-N=C=N-) in the molecule. The carbodiimide compound may include at least one selected from the group consisting of polycarbodiimide, monocarbodiimide and cyclic carbodiimide. The polycarbodiimide may include at least one of an aliphatic polycarbodiimide and an aromatic polycarbodiimide. The main chain of the aliphatic polycarbodiimide is composed of an aliphatic hydrocarbon. The main chain of the aromatic polycarbodiimide is composed of an aromatic hydrocarbon. The monocarbodiimide may include at least one of an aliphatic monocarbodiimide and an aromatic monocarbodiimide.
[0080] The monocarbodiimide contains, for example, at least one selected from the group consisting of N,N'-di-o-methylbenzoylcarbodiimide, N,N'-diphenylcarbodiimide, N,N'-di-2,6-dimethylphenylcarbodiimide, N,N'-bis(2,6-diisopropylphenyl)carbodiimide, N,N'-bis(propylphenyl)carbodiimide, N,N'-dioctyldecylcarbodiimide, N-triyl-N'-cyclohexylcarbodiimide, N,N'-di-2,2-di-tert-butylphenylcarbodiimide, N-triyl-N'-phenylcarbodiimide, N,N'-di-p-nitrophenylcarbodiimide, N,N'-di-p-aminophenylcarbodiimide, N,N'-di-p-hydroxyphenylcarbodiimide, N,N'-dicyclohexylcarbodiimide and N,N'-di-p-toluoylcarbodiimide.
[0081] Polycarbodiimide is, for example, a compound represented by the following formula.
[0082] R 2 -(-N=C=NR 1 -) m -R 3
[0083] In the formula, m R 1 Each R is independently a divalent aromatic group or an aliphatic group. 1 When it is an aromatic group, R 1 It may be substituted with at least one of an aliphatic substituent, an alicyclic substituent and an aromatic substituent having at least one carbon atom. These substituents may have a heteroatom, and these substituents may be substituted at least one ortho position of the aromatic group to which the carbodiimide group is bonded. 2 is an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 5 to 18 carbon atoms, an aryl group, an aralkyl group having 7 to 18 carbon atoms, or -R 4 -NH-COS-R 5 , -R 4 COOR 5 , -R 4 -OR 5 , -R 4 -N(R 5 )2. -R 4 -SR 5 , -R 4 -OH, -R 4 -NH2, -R 4 -NHR 5 , -R 4 -Epoxy, -R 4 -NCO, -R 4 -NHCONHR 5 , -R 4 -NHCONR 5 R6 or -R 4 -NHCOOR 7 . R 3 -N=C=N-aryl, -N=C=N-alkyl, -N=C=N-cycloalkyl, -N=C=N-aralkyl, -NCO, -NHCONHR 5 、-NHCONHR 5 R 6 、-NHCOOR 7 、-NHCOS-R 5 、-COOR 5 、-OR 5 , epoxy, -N(R 5 )2. -SR 5 , -OH, -NH2 or -NHR 5 . R 4 is a divalent aromatic group or an aliphatic group. 5 and R 6 Each is independently an alkyl group having 1 to 20 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, an aralkyl group having 7 to 18 carbon atoms, an oligo / polyethylene glycol, or an oligo / polypropylene glycol. 7 With R 5 The invention relates to a polyester-based group or a polyamide-based group. m is an integer greater than 2.
[0084] The polycarbodiimide includes, for example, at least one selected from the group consisting of poly(4,4'-dicyclohexylmethanecarbodiimide), poly(N,N'-di-2,6-diisopropylphenylcarbodiimide), and poly(1,3,5-triisopropylphenylene-2,4-carbodiimide). Examples of commercially available polycarbodiimides include at least one selected from the group consisting of aliphatic polycarbodiimide (Elastostab H-01 manufactured by Nisshinbo Chemical Inc.) and carbodiimide-modified isocyanate (CARBODILITE V-05 manufactured by Nisshinbo Chemical Inc.).
[0085] Cyclic carbodiimide has one carbodiimide group and a group (bonding group) bonded to both nitrogen atoms (the first nitrogen atom and the second nitrogen atom) in the carbodiimide group in one molecule. The bonding group is, for example, a divalent group selected from an aliphatic group, an alicyclic group, an aromatic group, and a group formed by a combination of these. The bonding group may also have a heteroatom. The aromatic group is, for example, selected from the group consisting of an arylene group having 5 to 15 carbon atoms, an aromatic triyl group having 5 to 15 carbon atoms, and an aromatic tetrayl group having 5 to 15 carbon atoms. The aliphatic group is, for example, selected from the group consisting of an alkylene group having 1 to 20 carbon atoms, an alkane triyl group having 1 to 20 carbon atoms, and an alkane tetrayl group having 1 to 20 carbon atoms. The alicyclic group is, for example, selected from the group consisting of a cycloalkylene group having 3 to 20 carbon atoms, a cycloalkane triyl group having 3 to 20 carbon atoms, and a cycloalkane tetrayl group having 3 to 20 carbon atoms.
[0086] The carbodiimide compound (H) preferably contains cyclic carbodiimide. In this case, there are advantages that the storage stability of the composition (X) is less likely to be impaired and the adhesive strength of the cured product is more easily improved.
[0087] The composition (X) may further contain additives other than those mentioned above without excessively impairing the effects of the present embodiment. The additives include at least one selected from the group consisting of free radical scavengers, diluents, solvents, flexibility imparting agents, coupling agents, antioxidants, thixotropy imparting agents (thixotropic agents) and dispersants.
[0088] The composition (X) can be prepared by mixing the components of the above-mentioned composition (X).
[0089] In the present embodiment, the L* value of the L*a*b* colorimetric system standardized by the International Commission on Illumination (CIE) in 1976 of the color of the cured product obtained by curing the composition (X) is preferably 5.0 or more and 30.0 or less. That is, preferably in a manner where the L* value of the L*a*b* colorimetric system of the color of the cured product becomes 5.0 or more and 30.0 or less, the composition of the composition (X), particularly the type and the amount of the black colorant (D), is adjusted. In the present embodiment, as described above, the refractive index of the alkene compound (A) has a specific relationship with the refractive index of the filler (C), and as a result, the L* value of the color of the cured product can be achieved by adjusting the composition (X), particularly the type and the amount of the black colorant (D), to be 5.0 or more and 30.0 or less. At this time, since the L* value is less than 30.0, the blackness of the color of the cured product can be particularly improved. In addition, even if the L* value of the cured product is less than 30.0, the composition (X) can still have good deep curability. In addition, when the L* value is 5.0 or more, it is easy to maintain the good deep curability of the composition (X) at a high level. The L* value is more preferably 5.5 or more, and more preferably 6.0 or more. In addition, the L* value is more preferably 29.0 or less, and more preferably 28.0 or less.
[0090] In the present embodiment, it is preferred that the cavity of a container having a cylindrical cavity with an inner diameter of 3 mm and a depth of 5 mm and an opening communicating with the cavity be filled with the composition (X) and the accumulated light intensity be 400 mJ / cm 2 Under the conditions of , when ultraviolet rays with a peak wavelength of 365nm are irradiated from the opening toward the surface of the composition (X) in the cavity, the composition (X) is partially cured with a thickness of 0.40mm or more in the depth direction from the surface. At this time, the composition (X) can have excellent deep curing properties. In addition, in the present embodiment, although the composition (X) contains a black colorant (D), since the refractive index of the olefin compound (A) has a specific relationship with the refractive index of the filler (C), the high deep curing properties of the composition (X) can still be achieved. It is more preferred that the thickness of the aforementioned cured portion is 0.42mm or more, and it is further preferred that it is 0.44mm or more. It should be noted that the details of the evaluation method of the deep curing property will be described in detail in the column of the embodiments disclosed later.
[0091] As described above, the composition (X) can be used as an adhesive. That is, a cured product can be obtained by curing the composition (X), and the cured product can be used to bond two components constituting a device (hereinafter also referred to as a first component and a second component), for example.
[0092] The cured product of the present embodiment is obtained by curing the composition (X). As described above, the first member and the second member can be bonded together using the cured product.
[0093] The device of the present embodiment comprises a first component, a second component and a cured product, wherein the cured product is between the first component and the second component, and the first component and the second component are bonded. The cured product is obtained by curing the composition (X). As described above, the device is, for example, an optical device such as a camera module, but is not limited thereto. For example, as a device, electronic components such as semiconductor elements, integrated circuits, large-scale integrated circuits, transistors, thyristors, diodes, capacitors, etc. can be listed. When the above-mentioned device is a camera module, the bonding of the first component to the second component is, in other words, bonding between the constituent components of the camera module. As examples of bonding of the first component to the second component, bonding of the substrate to the camera housing and bonding of the lens unit to the camera housing can be listed. It should be noted that the first component and the second component are not limited to these examples.
[0094] For example, the camera module includes an optical component and a component other than the optical component, namely a peripheral component. The optical component is, for example, the lens unit described above, and the peripheral component is, for example, the camera housing described above. The method for manufacturing the camera module includes, for example, an operation of bonding the optical component and the peripheral component using an adhesive. The adhesive is a photocurable composition containing a reaction-curable resin component, a filler (C), and a colorant (D). When the value of the refractive index of the reaction-curable resin component is set to dr, and the value of the refractive index of the filler (C) is set to df, dr and df satisfy the relationship shown in formula (1). The adhesive is, for example, the composition (X) described above.
[0095] -0.040<(df-dr)≤0.080 (1)
[0096] The materials of the first component and the second component are, for example, resin materials such as liquid crystal polymer, polycarbonate, polyester, polyimide, metals such as nickel, copper, ceramics, glass, or other various substrate materials, but are not limited to these.
[0097] A method for bonding a first member and a second member using the composition (X) and a method for producing a device including the first member, the second member, and a cured product will be described.
[0098] The composition (X) is placed between the first component and the second component. In this state, the composition (X) is irradiated with light so that the curing of the composition (X) is carried out to a certain extent. Thus, the first component and the second component can be temporarily bonded. The wavelength of the light irradiating the composition (X) at this time can be appropriately selected according to the type of free radical polymerization initiator (E) in the composition (X). The light is, for example, ultraviolet light. If the first component and the second component are temporarily bonded like this, it is easy to improve the alignment accuracy by appropriately adjusting the mutual positional relationship between the first component and the second component. Then, by heating the composition (X), the composition (X) is fully cured to make a cured product, and the first component and the second component are bonded using the cured product. The conditions for heating the composition (X) are appropriately set in a manner that the composition (X) can be fully cured. The heating conditions are, for example, a heating temperature of 80°C or more and 120°C or less, and a heating time of 30 minutes or more and 120 minutes or less.
[0099] It is also possible to produce a cured product by fully curing the composition (X) by irradiating the composition (X) with light without heating the composition (X). That is, it is also possible to produce a cured product by irradiating the composition (X) with light while the composition (X) is interposed between the first component and the second component, thereby allowing the curing reaction of the composition (X) to proceed sufficiently, and curing the composition (X) without heating the composition (X). In this case, the first component and the second component can also be bonded together using the cured product.
[0100] (Summarize)
[0101] The photocurable composition of the first embodiment of the present disclosure contains: a reaction curable resin component containing an olefin compound (A) and a thiol compound (B), a filler (C), a colorant (D), and a radical polymerization initiator (E). When the refractive index of the reaction curable resin component is dr and the refractive index of the filler (C) is df, dr and df satisfy the relationship shown in the following formula (1).
[0102] -0.040<(df-dr)≤0.080 (1)
[0103] In this manner, a photocurable composition can be obtained which contains an ene compound and a thiol compound and has good deep curability despite containing a black colorant.
[0104] The second aspect is the first aspect, wherein the percentage of the filler (C) relative to the photocurable composition is 5 mass % or more and 40 mass % or less.
[0105] A third aspect is the first or second aspect, wherein the refractive index of the filler (C) is 1.480 or more and 1.600 or less.
[0106] In this manner, the photocurable composition can have better deep curability and the blackness of the cured product can be further improved.
[0107] A fourth aspect is any one of the first to third aspects, wherein the filler (C) has a true specific gravity of 0.50 or more and 2.00 or less.
[0108] This makes it possible to suppress the floating of the filler (C) in the photocurable composition and to prevent the flexibility of the cured product from being impaired.
[0109] The fifth aspect is any one of the first to fourth aspects, wherein the percentage of the colorant (D) is 1.0 mass % or less based on the solid content in the photocurable composition.
[0110] In this manner, even if the percentage of the colorant (D) is 1.0 mass % or less, the blackness of the cured product can be sufficiently increased. Furthermore, the deep curability of the photocurable composition can be particularly improved.
[0111] The sixth aspect is any one of the first to fifth aspects, wherein the photocurable composition further contains a stabilizer (G).
[0112] This aspect can improve the storage stability of the photocurable composition.
[0113] According to a seventh aspect, in the sixth aspect, the stabilizer (G) contains a radical polymerization inhibitor.
[0114] This aspect can improve the storage stability of the photocurable composition.
[0115] According to an eighth aspect, in the sixth or seventh aspect, the photocurable composition further contains an anionic polymerization initiator (F), and the stabilizer (G) contains an anionic polymerization inhibitor.
[0116] This aspect can improve the storage stability of the photocurable composition.
[0117] A ninth aspect is any one of the first to eighth aspects, wherein the reaction-curable resin component further contains an epoxy compound (H).
[0118] The tenth embodiment is any one of the first to ninth embodiments, wherein a cavity of a container having a cylindrical cavity with an inner diameter of 3 mm and a depth of 5 mm and an opening communicating with the cavity is filled with a photocurable composition, and a photocurable composition is applied to the cavity at a cumulative light intensity of 400 mJ / cm 2 When ultraviolet rays with a peak wavelength of 365 nm are irradiated from the opening toward the surface of the photocurable composition in the cavity under the conditions of , the photocurable composition is cured in a portion having a thickness of 0.40 mm or more in a depth direction from the surface.
[0119] In this manner, the photocurable composition can have excellent deep curability, and although the photocurable composition contains the black colorant (D), high deep curability of the photocurable composition can be achieved.
[0120] In an eleventh aspect, in any one of the first to tenth aspects, the color L of the cured product of the photocurable composition is * a * b * L in the colorimetric system * The value is 5.0 or more and 30.0 or less.
[0121] In this manner, the blackness of the color of the cured product can be particularly improved, and the photocurable composition can have good deep curing properties.
[0122] According to a twelfth aspect, in any one of the first to eleventh aspects, the photocurable composition is an adhesive for bonding an optical component and a peripheral component in a camera module including the optical component and a peripheral component which is a component other than the optical component.
[0123] The manufacturing method of the camera module of the 13th embodiment is a manufacturing method of a camera module having an optical component and a component other than the optical component, i.e., a peripheral component. The manufacturing method of the camera module includes an operation of bonding the optical component and the peripheral component using an adhesive. The adhesive is a photocurable composition containing a reaction-curable resin component, a filler (C), and a colorant (D). When the refractive index value of the reaction-curable resin component is set to dr, and the refractive index value of the filler (C) is set to df, dr and df satisfy the relationship shown in the following formula (1).
[0124] -0.040<(df-dr)≤0.080 (1)
[0125] The fourteenth aspect is the thirteenth aspect, wherein the reaction-curable resin component contains an ene compound (A) and a thiol compound (B). The adhesive further contains a radical polymerization initiator (E).
[0126] Example
[0127] Hereinafter, more specific examples of this embodiment are presented. It should be noted that this embodiment is not limited to the following examples.
[0128] 1. Preparation of the composition
[0129] The compositions were prepared by mixing the raw materials shown in Tables 1 to 7. The details of the raw materials shown in Tables 1 to 7 are as follows.
[0130] It should be noted that the refractive index of the filler is a value obtained by the following measurement method. A mixture is prepared by mixing a liquid bisphenol A epoxy resin, a liquid bisphenol F epoxy resin and a filler. The refractive index of the mixture is measured at a test temperature of 25°C using Abbemat500 manufactured by Anton Paar. Next, the refractive index of each of the liquid bisphenol A epoxy resin and the liquid bisphenol F epoxy resin is measured in the same manner as described above. Using these values, the refractive index of the filler is calculated by the following formula.
[0131] df={dx-(dA×VA / 100)-(dF×VB / 100)} / (Vf / 100)
[0132] dA: refractive index of bisphenol A epoxy resin.
[0133] VA: ratio of bisphenol A type epoxy resin in the mixture (unit: volume %).
[0134] dF: refractive index of bisphenol F epoxy resin.
[0135] VF: ratio of bisphenol F type epoxy resin in the mixture (unit: volume %).
[0136] dx: refractive index of the mixture.
[0137] df: refractive index of filler.
[0138] Vf: ratio of filler in the mixture (unit: volume %).
[0139] (1) Olefin compounds
[0140] -M-313: Isocyanuric acid EO-modified di- and triacrylates. Produced by Toagosei Co., Ltd. Product name: ARONIX M-313. Functional group equivalent weight: 151.5.
[0141] -A-9300-1CL: a mixture of ε-caprolactone-modified tris-(2-acryloyloxyethyl)isocyanurate and tris-(2-acryloyloxyethyl)isocyanurate. Manufactured by Shin-Nakamura Chemical Co., Ltd. Product name: NK Ester A-9300-1CL. Functional group equivalent weight: 199.
[0142] -ABE-300: ethoxylated bisphenol A diacrylate. Produced by Shin-Nakamura Chemical Industry Co., Ltd. Product name: NKEster ABE-300. Functional group equivalent weight: 234.
[0143] -EA-0300: 9,9-bis(4-(2-(meth)acryloyloxyethoxy)phenyl)-9H-fluorene. Produced by Osaka Gas Chemicals Co., Ltd. Product name: OGSOL EA-0300. Functional group equivalent: 450.
[0144] (2) Epoxy compounds
[0145] -YD8125: Bisphenol A type epoxy resin. Made by NIPPON STEEL Chemical & Material Co., Ltd. Product No. YD8125. Functional group equivalent weight 175.
[0146] -YDF8170: Bisphenol F type epoxy resin. Made by NIPPON STEEL Chemical & Material Co., Ltd. Product No. YDF8170. Functional group equivalent weight 160.
[0147] (3) Thiol compounds
[0148] -PE1: Pentaerythritol tetrakis(3-mercaptobutyrate). Produced by Showa Denko K.K. Product name: Karenz MTPE1 (registered trademark). Functional group equivalent weight: 152.
[0149] -NR1: 1,3,5-tris(2-(3-thiobutanoyloxy)ethyl)-1,3,5-triazine-2,4,6-trione represented by the following formula. Manufactured by Showa Denko K.K. Product name: Karenz MTNR1 (registered trademark). Functional group equivalent (thiol group equivalent): 189.
[0150]
[0151] -SS32: 1,3,5-tris[3-(2-mercaptoethylthio)propyl]isocyanurate represented by the following formula. Produced by Kawaguchi Chemical Industry Co., Ltd. Product name: ACTOCURE SS32. Functional group equivalent weight: 177.
[0152]
[0153] -TS-G(L): A glycoluril derivative represented by the following formula. Produced by Shikoku Chemical Industry Co., Ltd. Product name: TS-G(L). Functional group equivalent weight: 96.
[0154]
[0155] (4) Free radical polymerization initiator
[0156] - Omnirad 184: 1-Hydroxycyclohexyl-phenyl ketone, manufactured by IGM Resins BV, trade name Omnirad 184.
[0157] -Omnirad TPO G: 2: 2,4,6-Trimethylbenzoyl-diphenylphosphine oxide, manufactured by IGM Resins BV, product name Omnirad TPO G.
[0158] (5) Anionic polymerization initiator
[0159] -HX3722: microencapsulated imidazole. Produced by Asahi Kasei E-Materials Co., Ltd. Product name: NOVACURE HX3722.
[0160] (6) Stabilizer
[0161] -Q1301: Free radical polymerization inhibitor. N-nitroso-N-phenylhydroxylamine aluminum. Made by Fujifilm Wako Pure Chemical Industries, Ltd. Product name Q-1301.
[0162] -Tributyl borate: anionic polymerization inhibitor.
[0163] (7) Filling
[0164] -KMP-605: Silicone composite powder. Made by Shin-Etsu Chemical Co., Ltd. Product name KMP-605. Average particle size 2 μm. Refractive index 1.47. True specific gravity 0.99.
[0165] -KMP-706: Silicone resin powder. Made by Shin-Etsu Chemical Co., Ltd. Product name KMP-706. Average particle size 2 μm. Refractive index 1.47. True specific gravity 1.30.
[0166] -KMP-708: Phenyl-modified silicone resin powder. Made by Shin-Etsu Chemical Co., Ltd. Product name KMP-708. Average particle size 2 μm. Refractive index 1.49. True specific gravity 1.32.
[0167] -KMP-597: Silicone rubber powder. Made by Shin-Etsu Chemical Co., Ltd. Product name KMP-597. Average particle size 5 μm. Refractive index 1.57. True specific gravity 0.97.
[0168] -MZ-100: Core-shell type butadiene rubber powder. Manufactured by Kaneka Co., Ltd. Product name: MZ-100. Average particle size: 150 μm. Refractive index: 1.56. True specific gravity: 1.10.
[0169] -MZ-120: Core-shell type butadiene rubber powder. Manufactured by Kaneka Co., Ltd. Product name: MZ-120. Average particle size: 150 μm. Refractive index: 1.54. True specific gravity: 1.10.
[0170] -EP-5500: Silicone powder. Made by Dow Toray Co., Ltd. Product name: DOWSIL EP-5500 Powder. Average particle size: 3 μm. Refractive index: 1.57. True specific gravity: 0.98.
[0171] -EP-5518: Silicone powder. Made by Dow Toray Co., Ltd. Product name: DOWSIL EP-5518. Average particle size: 3 μm. Refractive index: 1.57. True specific gravity: 0.98.
[0172] -GS-0605-S: Polystyrene powder. Made by AICAKOGYO CO..LTD. Product name: Ganzpearl GS-0605-S. Average particle size: 6 μm. Refractive index: 1.58. True specific gravity: 1.05.
[0173] -EPOSTAR MV1004: Acrylic powder. Made by Nippon Shokubai Co., Ltd. Product name: EPOSTAR MV1004. Average particle size: 4 μm. Refractive index: 1.51. True specific gravity: 1.20.
[0174] -EPOSTAR MS: Benzoguanamine resin powder. Made by Nippon Shokubai Co., Ltd. Product name: EPOSTAR MS. Average particle size: 2 μm. Refractive index: 1.60. True specific gravity: 1.40.
[0175] -SE5050: Spherical silica. Made by Admatechs Company Limited. Product name SE5050. Average particle size 1 μm. Refractive index 1.47. True specific gravity 2.20.
[0176] (8) Black colorant
[0177] -TM-B: titanium black. Made by Akaho Chemical Co., Ltd. Product name TM-B.
[0178] -13M-C: Titanium black. Made by Mitsubishi Materials Corporation. Product name: Titanium Black 13M-C.
[0179] (9) Carbodiimide compounds
[0180] -TCC-FP20M: Powdered cyclic carbodiimide. Produced by Teijin Limited. Product name: CARBOSITA TCC-FP20M.
[0181] (10) Additives
[0182] -A-187J: Silane coupling agent. Silquest A-187J manufactured by Momentive.
[0183] 2. Evaluation test
[0184] (1) Evaluation of deep curing properties
[0185] The composition was filled in the cavity of a container having a cylindrical cavity with an inner diameter of 3 mm and a depth of 5 mm and an opening on the upper surface communicating with the cavity. EXECURE-H-1VC manufactured by HOYA Corporation was used and the cumulative light intensity was 4000 mJ / cm 2 Under the conditions of , the surface of the composition in the cavity is irradiated with ultraviolet rays having a peak wavelength of 365 nm.
[0186] Next, the composition was taken out from the cavity, and the surface of the cured portion of the composition was wiped with paper to remove the uncured portion from the cured portion. The thickness of the cured portion was measured with a digital vernier caliper. The results are shown in Tables 1 to 7.
[0187] (2) Appearance color evaluation
[0188] A release film made of polyethylene terephthalate was placed on a glass plate, and a silicone spacer with a 30 mm × 30 mm open space and a thickness of 0.5 mm was placed on the release film. After the space in the spacer was filled with the composition, a release film made of polyethylene terephthalate was placed on the upper surface of the spacer, and a glass plate was placed on the release film. At an accumulated light intensity of 4000 mJ / cm 2 Under the conditions of , ultraviolet rays with a peak wavelength of 365 nm were irradiated from above the upper glass plate toward the composition in the space to produce a cured product.
[0189] The L* value of the L*a*b* colorimetric system of the surface color of the cured product was measured by using a CM-5 model manufactured by Konica Minolta, Inc., excluding specular reflection light. The results are shown in Tables 1 to 7.
[0190] (3) Elastic modulus
[0191] A release film made of polyethylene terephthalate was placed on a glass plate, and a silicone spacer with a 5 mm × 50 mm open space and a thickness of 0.5 mm was placed on the release film. After the space in the spacer was filled with the composition, a release film made of polyethylene terephthalate was placed on the upper surface of the spacer, and a glass plate was placed on the release film. At an accumulated light intensity of 4000 mJ / cm 2 Under the conditions of , ultraviolet rays with a peak wavelength of 365nm were irradiated from above the upper glass plate toward the composition in the space. Next, the composition was heated at 80°C for 1 hour to produce a cured product. For the cured product, the tensile method of the dynamic viscoelasticity test (DMA) was performed based on JIS K7244-4. The dynamic viscoelasticity test (DMA) was performed using model DMA7100 manufactured by Hitachi High-Tech Corporation as a measuring device at a frequency of 1.0 Hz and a heating rate of 10°C / min. From the results, the maximum value of the elastic modulus of the cured product in the range of -60°C to 260°C was calculated. The results are shown in Tables 1 to 7.
[0192] (4) Bonding strength #1
[0193] A test piece made of a liquid crystal polymer and having a smooth surface (product name: E463i, manufactured by Polyplastics Co., Ltd.) was prepared. The arithmetic mean roughness Ra (JIS B0601) of the surface of the test piece was 0.47 μm.
[0194] The composition was applied to the surface of the test piece to form a film with a diameter of 5 mm and a thickness of 0.5 mm. 2 The film was irradiated with ultraviolet light having a peak wavelength of 365 nm under the conditions of , and then heated at 80°C for 1 hour to produce a cured product. Next, the shear bonding strength of the cured product to the test piece was measured using a shear tester (manufactured by Nordson, model DAGE4000 Optima) at a test temperature of 25°C, a test speed of 0.1 mm / sec, and a test height of 50 μm. The results are shown in Tables 1 to 7.
[0195] (5) Bonding strength #2
[0196] A test piece made of a liquid crystal polymer and having a smooth surface (product name: E463i, manufactured by Polyplastics Co., Ltd.) was prepared. The arithmetic mean roughness Ra (JIS B0601) of the surface of the test piece was 0.47 μm.
[0197] The composition was applied to the surface of the test piece to prepare a film with a diameter of 5 mm and a thickness of 0.5 mm. The film was heated at 80°C for 1 hour to prepare a cured product. Next, a shear tester (manufactured by Nordson, model DAGE4000 Optima) was used to measure the shear bonding strength of the cured product to the test piece under the conditions of a test temperature of 25°C, a test speed of 0.1 mm / sec, and a test height of 50 μm. The results are shown in Tables 1 to 7.
[0198] [Table 1]
[0199]
[0200] [Table 2]
[0201]
[0202] [Table 3]
[0203]
[0204] [Table 4]
[0205]
[0206] [Table 5]
[0207]
[0208] [Table 6]
[0209]
[0210] [Table 7]
[0211]
Claims
1. A photocurable composition comprising: A reaction-curable resin component containing an ene compound (A) and a thiol compound (B), Filler (C), Colorant (D) and Free radical polymerization initiator (E), When the refractive index of the reaction-curable resin component is dr and the refractive index of the filler (C) is df, dr and df satisfy the relationship represented by the following formula (1): -0.040<(df-dr)≤0.080 (1).
2. The photocurable composition according to claim 1, wherein The percentage of the filler (C) relative to the photocurable composition is 5 mass % or more and 40 mass % or less.
3. The photocurable composition according to claim 1 or 2, wherein The refractive index of the filler (C) is 1.480 or more and 1.600 or less.
4. The photocurable composition according to claim 1 or 2, wherein The true specific gravity of the filler (C) is 0.50 or more and 2.00 or less.
5. The photocurable composition according to claim 1 or 2, wherein The percentage of the colorant (D) relative to the solid content in the photocurable composition is 1.0 mass % or less. The photocurable composition according to claim 1 or 2, further comprising a stabilizer (G).
7. The photocurable composition according to claim 6, wherein The stabilizer (G) contains a radical polymerization inhibitor.
8. The photocurable composition according to claim 6, further comprising an anionic polymerization initiator (F), The stabilizer (G) contains an anionic polymerization inhibitor.
9. The photocurable composition according to claim 1 or 2, wherein The reaction-curable resin component further contains an epoxy compound (H).
10. The photocurable composition according to claim 1 or 2, wherein In a state where a container having a cylindrical cavity with an inner diameter of 3 mm and a depth of 5 mm and an opening communicating with the cavity is filled with the photocurable composition, a photocurable composition is applied to the cavity at a cumulative light intensity of 400 mJ / cm 2 Under the conditions of, when ultraviolet rays with a peak wavelength of 365 nm are irradiated from the opening toward the surface of the photocurable composition in the cavity, the photocurable composition is cured in a portion having a thickness of 0.40 mm or more in a depth direction from the surface.
11. The photocurable composition according to claim 1 or 2, wherein The L* value of the L*a*b* colorimetric system of the color of the cured product is 5.0 or more and 30.0 or less. 12 . The photocurable composition according to claim 1 , which is an adhesive for bonding an optical component and a peripheral component in a camera module including an optical component and a component other than the optical component.
13. A method for manufacturing a camera module, comprising: an optical component and components other than the optical component, namely, peripheral components; The method comprises the steps of bonding the optical component and the peripheral component using an adhesive. The adhesive is a photocurable composition containing a reaction-curable resin component, a filler (C) and a colorant (D). When the refractive index of the reaction-curable resin component is dr and the refractive index of the filler (C) is df, dr and df satisfy the relationship represented by the following formula (1): -0.040<(df-dr)≤0.080 (1).
14. The method for manufacturing a camera module according to claim 13, wherein: The reaction-curable resin component contains an ene compound (A) and a thiol compound (B), The adhesive further contains a radical polymerization initiator (E).